2021
DOI: 10.31532/interdiscipeducpsychol.2.3.005
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Enthusiasm, Supportive Instructional Practices, and Student Motivation in Mathematics Classrooms

Abstract: This longitudinal study examined the relations between teacher enthusiasm, supportive instructional practices, and students’ mastery goal orientation and behavioral engagement in mathematics. All variables were assessed by means of student reports. A total of 751 9th and 10th grade secondary school students from 46 mathematics classrooms were presented with questionnaires at the beginning (Time 1) and the middle of the school year (Time 2). Structural equation analyses revealed that student-perceived teacher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Besides SDT, three (around 10%) studies referred to social-cognitive theories (Ruzek and Schenke, 2019 ) or stage–environment fit theory (Yu et al, 2015 , 2016 ) to underpin their studies. In addition, seven articles were unclear on the underpinning theories (e.g., Kiefer and Pennington, 2017 ; Frommelt et al, 2021 ). See Table 8 below.…”
Section: Resultsmentioning
confidence: 99%
“…Besides SDT, three (around 10%) studies referred to social-cognitive theories (Ruzek and Schenke, 2019 ) or stage–environment fit theory (Yu et al, 2015 , 2016 ) to underpin their studies. In addition, seven articles were unclear on the underpinning theories (e.g., Kiefer and Pennington, 2017 ; Frommelt et al, 2021 ). See Table 8 below.…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 14 A longitudinal study revealed that students who rate their teachers as enthusiastic feel that their basic needs for autonomy, competence, and social relationships are more strongly supported. 15 Teachers’ enthusiasm motivates students and therefore improves their recall scores. 16 Similarly, Moè et al found that when information is delivered with enthusiasm, it can increase the level of intrinsic motivation and positive emotions of students, as well as their performance on recall tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The classroom is an emotional space, and teachers’ emotions occupy the heart of teaching (Agudo, 2018 ; Hargreaves, 2000 ). In classrooms, teachers are encouraged to display positive emotions (e.g., enthusiasm) to benefit students’ learning outcomes, such as motivation (Frenzel et al, 2019 ; Frommelt et al, 2021 ), memory performance (Moè, 2016 ), and academic achievements (Moè et al, 2021 ). However, chronically presenting inauthentic emotions may cause strain or even emotional exhaustion for teachers (Carroll et al, 2022 ; Lee, 2019 ; Taxer & Frenzel, 2018 ).…”
Section: Introductionmentioning
confidence: 99%